A Retrospective Chart Review on the Role of Suppressive Therapy in the Management of Spinal Infections Involving Hardware. (25th June 2020) - Beydoun, Nour; Tandon, Sonia; Krengel, Sonia; Johnson, Eric; Palacio Bedoya, Federico; Moore, Michael; Refai, Daniel; Rouphael, Nadine
Abstract: Background: One percent to 8% of patients undergoing spinal instrumentation surgeries develop infections. There is no consensus on the medical and surgical management of these infections. Methods: We conducted a retrospective chart review based on International Classification of Diseases, Ninth Revision, and Common Procedural Terminology codes relevant to spinal infections with hardware within Emory Healthcare over a 10-year period. Extracted data included patient demographics, clinical presentation, laboratory and microbiologic results, and surgical and medical management including choice and duration of suppressive therapy. Multivariable logistic regression was used to assess the association of length of use of suppressive antibiotics with treatment success and to identify predictors of use of suppressive antibiotics. Results: Of 869 records, 124 met inclusion criteria. Fifty patients (40.3%) had an infection that occurred after hardware placement, mostly within 3 months postsurgery, while the remainder had vertebral osteomyelitis that required hardware placement. After initial intravenous antibiotic treatment for ≥4 weeks, 72 patients (64.5%) were given suppressive antibiotics. The overall treatment success rate was 78.2%. In spinal infections involving hardware with gram-negative rods, patients were less likely to receive suppressive antibiotics, less likely to have hardware removed, and less likely to have treatment success compared with patients with infections with Staphylococcus species. Conclusions: Management of spinal infections involving hardware should be tailored to the timing of onset of infection and causative organism. Further studies are needed to determine best management practices, particularly for gram-negative rod infections where the role of further suppressive antibiotics and hardware removal may be warranted.